THE ROLE AND PROSPECTS OF IPO AND SPO PRACTICES IN THE DEVELOPMENT OF FINANCIAL MARKETS - Alikulova Nigora Tuygunovna (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
In recent years, the development of the capital market has been identified as a key priority in Uzbekistan’s economic policy. In the process of modernizing the national economy, reducing the state’s share, and expanding the private sector, the practices of Initial Public Offering (IPO) and Secondary Public Offering (SPO) have emerged as important instruments. Global experience shows that IPOs are among the most transparent and effective means of raising capital, enabling households’ savings to be channeled into the real sector of the economy. SPOs, in turn, allow companies to mobilize additional resources under market conditions, increase market liquidity, and reduce the state’s ownership stake.